2022
DOI: 10.1038/s41514-022-00082-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA oxidative mutations are elevated in Mexican American women potentially implicating Alzheimer’s disease

Abstract: Mexican Americans (MAs) are the fastest-growing Hispanic population segment in the US; as this population increases in age, so will the societal burden of age-related diseases such as Alzheimer’s disease (AD). Mitochondrial DNA (mtDNA) damage may be implicated in MA AD risk since metabolic comorbidities are more prevalent in this group. Oxidative damage to guanosine (8oxoG) is one of the most prevalent DNA lesions and a putative indicator of mitochondrial dysfunction. Testing blood samples from participants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…AD disproportionately affects Hispanics/Latinos compared to NHWs; this is thought to be due to the increased prevalence of metabolic syndrome, obesity, cardiovascular health risks, and diabetes 9,17,18 . These observations combined with our previous data indicating MAs have elevated levels of oxidative damage compared to NHWs, leads us to the premise that mitochondrial health may hold greater biological importance in the development of age-related disease for individuals with Hispanic/Latinx ancestry 19 .…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…AD disproportionately affects Hispanics/Latinos compared to NHWs; this is thought to be due to the increased prevalence of metabolic syndrome, obesity, cardiovascular health risks, and diabetes 9,17,18 . These observations combined with our previous data indicating MAs have elevated levels of oxidative damage compared to NHWs, leads us to the premise that mitochondrial health may hold greater biological importance in the development of age-related disease for individuals with Hispanic/Latinx ancestry 19 .…”
Section: Introductionmentioning
confidence: 73%
“…Our mtDNA CN and cf-mtDNA data can be considered as a proxy for our more recent data evaluating mitochondrial 8oxoG variant load since it does not capture if mutation has occurred. More recently in a similar population-based cohort, we discovered that mtDNA variants indicative of 8oxoG were signi cantly elevated in MAs compared to NHWs and was associated with sex, education, and suggestive for cognitive function 19 . Correspondingly, Miller, et al, revealed AD neurons compared to age-matched controls had signi cantly elevated levels of somatic single nucleotide variants (sSNVs) than anticipated when considering sSNVs are known to increase with age 32 , and the distribution of the variants are presumed to occur secondary to developing disease pathology 32 .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In Mexican Americans, the mtDNA 8oxoG mutation load was significantly higher when compared to non-Hispanic whites. Haplogroups A and C exhibited higher 8oxoG variant counts, while haplogroups I and K exhibited lower 8oxoG variant counts [ 61 ]. All these findings suggest that mtDNA haplogroups are associated with the risk of AD, but it is highly specific to populations.…”
Section: Mtdna Mutationmentioning
confidence: 99%